Tindakan Politik Perempuan PKS Dalam Kaderisasi - Horidatul Bakiyah (Jurnal Komunikasi, 2018)
Humans act with regard to all things and directs its behavior observed in the act as it is interpreted. The political actors are women who are on the Islamic-based political organization that PKS run regeneration. Recruitment function as a function that is executed in the PKS women regeneration. The involvement of women in the political sphere and democracy should be a requirement, so as to give birth to the protection of the rights and interests of women. This study using Alfred Scutz theory that social science thinking is closely related to various forms of interaction which is essentially political communication in society that women's political action. The symptoms in the social world is nothing but an object of formal study (focus of interest) of social phenomenology, namely the women's first political action, which is both a motive for the actions, and the third mainstreaming women's consciousness. The paradigm used in this research were interpretative paradigm and approach used is a qualitative approach , whereas the method used in this study is the phenomenological method. In this study  the writes found that in women's political action PKS divided into three normative action , aggressive action , and collaborative action . While the women's political motives are involved and merged into PKS divided into two , in order to motive and because motive . And women's political consciousness of PKS in the regeneration grouped into consciousness supervision ( on the surface ) and consciousness underground ( below the surface ) Keywords: Actions, Motif, Consciousness, Politics, Women, Regeneration